Empowering local creativity: the business potential of banana bark paintings - Muharzie, Rainhard; Mulyadi, Aris; Mulyati, Sri; Agustina, Fenny (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Banana bark, often considered agricultural waste, can be transformed into valuable works of art through creativity and innovation. This project, conducted in RW 21, Mangsang Village, Sei Beduk District, collaborated with Mr. Suyadi, a local artisan specializing in collage paintings made from banana bark. To enhance market reach, the community service team implemented offline marketing strategies by organizing a bazaar at Harbour Bay Batam and distributing brochures, while also utilizing Instagram for online promotion (@mcc.pelepahpisang). The results demonstrated increased public interest in sustainable art, despite challenges such as unfavorable weather conditions during the activities. This initiative contributed to the growth of community based creative economies and raised awareness of the potential of agricultural waste as a high value resource in local and global markets.